Beta-FeOOH nanorod loaded graphene composite material and preparation method thereof
The β-FeOOH nanorods are self-assembled and modified by phosphorylated graphene to form a graphene-loaded composite material, which solves the problem of low efficiency in removing dye pollutants in dye wastewater in the prior art, and achieves an efficient visible light photocatalytic degradation effect.
Patent Information
- Application Number
- CN202411637079.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art has problems such as high cost, low efficiency and poor stability when removing dye pollutants in dye wastewater, especially the catalytic degradation technology of visible light is limited by the proportion of visible light part of sunlight.
The β-FeOOH nanorods are self-assembled and modified and supported by phosphorylated graphene to form a composite material of β-FeOOH nanorods supported by graphene. The porous structure of graphene and the photocatalytic properties of β-FeOOH nanorods are used to form a heterogeneous photocatalytic system to synergistically remove dye pollutants.
The efficient degradation and removal rates of dyes such as methylene blue, methyl orange, rhodamine B in dye wastewater were achieved, reaching 99.6%, 97.8%, and 96.3%, respectively, and the biotoxicity of the dye was eliminated.
Smart Images

Figure BDA0005137384530000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanomaterials, and in particular relates to a composite material of beta-FeOOH nanorods loaded with graphene and a preparation method thereof. Background Art
[0002] As a typical wastewater pollution source, dye wastewater has become an environmental problem that needs to be solved urgently due to its high chroma, high salinity, difficulty in degradation and serious biological toxicity. Textile, papermaking and other industrial enterprises are the main sources of dye wastewater. The large-scale discharge of dyes into the water environment not only affects the appearance, but also causes toxicity to many organisms and threatens their health.
[0003] At present, there are many methods for removing dyes from wastewater, such as chemical oxidation, membrane separation, biodegradation, adsorption, photocatalysis, etc. Chemical oxidation uses strong oxidants such as O 3 , Fenton reagent, etc., which has obvious effect in treating wastewater, but the cost of oxidants is high and the technical equipment requirements are high; membrane separation method is to treat dye wastewater by synthetic membrane filtration, but the membrane is easy to be blocked after long-term operation, resulting in a decrease in membrane permeability, and the membrane components need to be replaced frequently, resulting in high operating costs. These problems make membrane separation technology have certain limitations in practical applications; although the biodegradation method is low-cost and has no secondary pollution, the biological system has low treatment efficiency and poor operating stability, which limits the application of biological methods to treat dye wastewater. Although the adsorption method for treating dye wastewater will not be affected by water volume and impact, there are still many residual dye pollutants after treatment, which is difficult to be widely used.
[0004] Photocatalytic oxidation using solar energy to treat dye wastewater is an important direction of current water treatment technology development. In recent years, literature has reported on the use of ultraviolet light to catalytically degrade dye molecules in water. However, ultraviolet light only accounts for 3-5% of sunlight, while visible light accounts for about 43% of sunlight, thus limiting the scope of application of solar photocatalysis. Currently, research on visible light catalytic degradation of water pollutants is more realistic. Summary of the invention
[0005] Based on the above technical problems, the present invention proposes a composite material of β-FeOOH nanorods loaded with graphene and a preparation method thereof, wherein the β-FeOOH nanorods are self-assembled, modified and loaded with phosphated graphene, so that the prepared composite material of β-FeOOH nanorods loaded with graphene has excellent performance in visible light photocatalytic degradation of dye pollutants in water.
[0006] The present invention provides a method for preparing a β-FeOOH nanorod-loaded graphene composite material, comprising the following steps:
[0007] S1, subjecting the amination-treated graphene to a phosphorylation reaction with phosphorous acid and an organic aldehyde to obtain phosphorylated graphene;
[0008] S2. Adding β-FeOOH nanorods into the dispersion of phosphated graphene to carry out a self-assembly reaction, thereby obtaining the β-FeOOH nanorod-loaded graphene composite material.
[0009] In the present invention, after the amination graphene is subjected to phosphorylation treatment, graphene with phosphate groups on the surface is obtained, and the phosphate ions generated by the hydrolysis of the graphene can effectively adsorb and wrap the β-FeOOH nanorods, and the β-FeOOH nanorods are controlled to form self-assembly deposition on the graphene surface, and finally the β-FeOOH nanorods can be effectively loaded on the graphene surface, thereby obtaining the composite material of the β-FeOOH nanorods loaded with graphene.
[0010] In the present invention, the structure of the phosphorylated graphene is shown as follows:
[0011]
[0012] Preferably, in step S1, the amination graphene is obtained by bonding graphene oxide with a polyamine and then reducing it;
[0013] Preferably, the polyamine is at least one of ethylenediamine, butanediamine, hexamethylenediamine or diethylenetriamine.
[0014] Preferably, in step S1, the organic aldehyde is at least one of formaldehyde, acetaldehyde, propionaldehyde or butyraldehyde.
[0015] Preferably, in step S1, the mass ratio of the amination graphene to the phosphorous acid and the organic aldehyde is 1:1-5:1-5.
[0016] Preferably, in step S2, the β-FeOOH nanorods are obtained by adding soluble iron salts into water and performing a hydrolysis reaction;
[0017] Preferably, the hydrolysis reaction further comprises adding cetyltrimethylammonium bromide.
[0018] Preferably, in step S2, the mass ratio of the dispersion liquid of β-FeOOH nanorods and phosphated graphene is 1:2-5.
[0019] Preferably, in step S2, the temperature of the self-assembly reaction is 130-160° C., and the time is 6-12 h.
[0020] The present invention also provides a β-FeOOH nanorod-loaded graphene composite material prepared by the preparation method.
[0021] The present invention also proposes an application of the β-FeOOH nanorod-loaded graphene composite material in catalytic degradation of dye pollutants.
[0022] Compared with the prior art, the present invention has the following technical effects:
[0023] The present invention utilizes phosphorylated graphene to perform self-assembly deposition on beta-FeOOH nanorods. In the obtained composite material of beta-FeOOH nanorods loaded with graphene, the beta-FeOOH nanorods can be effectively loaded on the surface of the graphene. On the one hand, the porous structure of the graphene can be utilized to effectively load the dye pollutants. On the other hand, the beta-FeOOH nanorods, hydrogen peroxide and visible light constitute a heterogeneous photocatalytic system. The synergistic effect of the three can have a high degradation and removal effect on the dye in the wastewater and can eliminate its biological toxicity. DETAILED DESCRIPTION
[0024] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0025] Example 1
[0026] A method for preparing a β-FeOOH nanorod-loaded graphene composite material comprises the following steps:
[0027] (1) adding graphite powder and potassium permanganate in a mass ratio of 1:1 to a mixed acid prepared by sulfuric acid and phosphoric acid in a volume ratio of 8:1, heating and stirring in a water bath at 50°C for 2 hours, then adding hydrogen peroxide to reduce the excess potassium permanganate, filtering the resulting suspension, washing, drying, and grinding into powder to obtain graphene oxide; adding the graphene oxide to N-methylpyrrolidone, ultrasonically dispersing it, adding ethylenediamine in an amount of 30 wt% of the mass of the graphene oxide, stirring and reacting at 80°C for 6 hours, then adding a hydrazine hydrate solution of the same mass as the graphene oxide for reduction, stirring and reacting at 90°C for 5 hours, filtering, washing, and obtaining amino graphene;
[0028] (2) adding phosphorous acid to concentrated hydrochloric acid and mixing evenly, then adding 50 wt% of the mass of phosphorous acid to the amino graphene, heating to 80° C. and then adding formaldehyde solution dropwise, wherein the amount of formaldehyde is 1.2 times the mass of phosphorous acid, stirring and refluxing for 12 h, filtering, washing with water, and vacuum drying to obtain phosphorylated graphene;
[0029] (3) adding ferric chloride hexahydrate to deionized water to completely dissolve the solution, adding cetyltrimethylammonium bromide twice the mass of ferric chloride hexahydrate, and then adding concentrated ammonia water to adjust the pH to 2, and after ultrasonic dispersion, heating to 90° C. and keeping the temperature for hydrolysis reaction for 16 hours, centrifugation, and drying to obtain β-FeOOH nanorods;
[0030] (4) Add the above-mentioned phosphated graphene to deionized water and stir and disperse it evenly to obtain 0.05 g / mL of phosphated graphene dispersion; then add the above-mentioned β-FeOOH nanorods to deionized water and stir and disperse it evenly to obtain 0.1 g / mL of β-FeOOH nanorod dispersion; add the β-FeOOH nanorod dispersion to the phosphated graphene dispersion at a volume ratio of 1:6, ultrasonically disperse it evenly, react at 150°C for 10 hours, centrifuge, wash, and dry to obtain the β-FeOOH nanorod-loaded graphene composite material.
[0031] The prepared β-FeOOH nanorod-loaded graphene composite material is used to catalyze the degradation of dye pollutants:
[0032] Add 5 mL of 30 wt% H into 100 mL of 200 mg / L dye wastewater. 2 O 2 Water and 0.25g of the above-mentioned β-FeOOH nanorod-loaded graphene composite material are reacted under natural light at room temperature. The reaction is mixed evenly with a magnetic stirrer during the reaction. Samples are taken 12 hours after the start of the reaction, and the upper clear liquid is taken and its absorbance is measured. The degradation rate is calculated based on the change in absorbance before and after the reaction. Finally, the removal rates of 200mg / L methylene blue, methyl orange, and rhodamine B dye wastewater are measured to be 99.6%, 97.8%, and 96.3%, respectively.
[0033] Example 2
[0034] A method for preparing a β-FeOOH nanorod-loaded graphene composite material comprises the following steps:
[0035] (1) adding graphite powder and potassium permanganate in a mass ratio of 1:1 to a mixed acid prepared by sulfuric acid and phosphoric acid in a volume ratio of 8:1, heating and stirring in a water bath at 50°C for 2h, then adding hydrogen peroxide to reduce the excess potassium permanganate, filtering the obtained suspension, washing, drying, and grinding into powder to obtain graphene oxide; adding the graphene oxide to N-methylpyrrolidone, ultrasonically dispersing it, adding 10wt% of ethylenediamine and 25wt% of hexamethylenediamine by weight of the graphene oxide, stirring and reacting at 80°C for 6h, then adding a hydrazine hydrate solution of the same weight as the graphene oxide for reduction, stirring and reacting at 90°C for 5h, filtering, washing, and obtaining amino graphene;
[0036] (2) adding phosphorous acid to concentrated hydrochloric acid and mixing evenly, then adding 50 wt% of the mass of phosphorous acid to the amino graphene, heating to 80° C. and then adding acetaldehyde solution dropwise, wherein the amount of acetaldehyde is 1.5 times the mass of phosphorous acid, stirring and refluxing for 12 h, filtering, washing with water, and vacuum drying to obtain phosphorylated graphene;
[0037] (3) adding ferric chloride hexahydrate to deionized water to completely dissolve the solution, adding cetyltrimethylammonium bromide twice the mass of ferric chloride hexahydrate, and then adding concentrated ammonia water to adjust the pH to 2, and after ultrasonic dispersion, heating to 90° C. and keeping the temperature for hydrolysis reaction for 16 hours, centrifugation, and drying to obtain β-FeOOH nanorods;
[0038] (4) Add the above-mentioned phosphated graphene to deionized water and stir and disperse it evenly to obtain 0.05 g / mL of phosphated graphene dispersion; then add the above-mentioned β-FeOOH nanorods to deionized water and stir and disperse it evenly to obtain 0.1 g / mL of β-FeOOH nanorod dispersion; add the β-FeOOH nanorod dispersion to the phosphated graphene dispersion at a volume ratio of 1:4, ultrasonically disperse it evenly, react at 130°C for 12 hours, centrifuge, wash, and dry to obtain the β-FeOOH nanorod-loaded graphene composite material.
[0039] The prepared β-FeOOH nanorod-loaded graphene composite material is used to catalyze the degradation of dye pollutants:
[0040] Add 5 mL of 30 wt% H into 100 mL of 200 mg / L dye wastewater. 2 O 2 Water and 0.25g of the above-mentioned β-FeOOH nanorod-loaded graphene composite material are reacted under natural light at room temperature. The reaction is mixed evenly with a magnetic stirrer during the reaction. Samples are taken 12 hours after the start of the reaction, and the upper clear liquid is taken and its absorbance is measured. The degradation rate is calculated based on the change in absorbance before and after the reaction. Finally, the removal rates of 200mg / L methylene blue, methyl orange, and rhodamine B dye wastewater are measured to be 99.1%, 98.0%, and 95.8%, respectively.
[0041] Example 3
[0042] A method for preparing a β-FeOOH nanorod-loaded graphene composite material comprises the following steps:
[0043] (1) adding graphite powder and potassium permanganate in a mass ratio of 1:1 to a mixed acid prepared by sulfuric acid and phosphoric acid in a volume ratio of 8:1, heating and stirring in a water bath at 50°C for 2h, then adding hydrogen peroxide to reduce the excess potassium permanganate, filtering the obtained suspension, washing, drying, and grinding into powder to obtain graphene oxide; adding the graphene oxide to N-methylpyrrolidone, ultrasonically dispersing it, adding diethylenetriamine in an amount of 30wt% of the mass of the graphene oxide, stirring and reacting at 80°C for 6h, then adding a hydrazine hydrate solution of the same mass as the graphene oxide for reduction, stirring and reacting at 90°C for 5h, filtering, washing, and obtaining amino graphene;
[0044] (2) adding phosphorous acid to concentrated hydrochloric acid and mixing evenly, then adding 50 wt% of the mass of phosphorous acid to the amino graphene, heating to 80° C. and then adding formaldehyde solution dropwise, wherein the amount of formaldehyde is 1.2 times the mass of phosphorous acid, stirring and refluxing for 12 h, filtering, washing with water, and vacuum drying to obtain phosphorylated graphene;
[0045] (3) adding ferric chloride hexahydrate to deionized water to completely dissolve the solution, adding cetyltrimethylammonium bromide twice the mass of ferric chloride hexahydrate, and then adding concentrated ammonia water to adjust the pH to 2, and after ultrasonic dispersion, heating to 90° C. and keeping the temperature for hydrolysis reaction for 16 hours, centrifugation, and drying to obtain β-FeOOH nanorods;
[0046] (4) Add the above-mentioned phosphated graphene to deionized water and stir and disperse it evenly to obtain 0.05 g / mL of phosphated graphene dispersion; then add the above-mentioned β-FeOOH nanorods to deionized water and stir and disperse it evenly to obtain 0.1 g / mL of β-FeOOH nanorod dispersion; add the β-FeOOH nanorod dispersion to the phosphated graphene dispersion at a volume ratio of 1:10, after ultrasonic dispersion, react at 160°C for 6 hours, centrifuge, wash, and dry to obtain the β-FeOOH nanorod-loaded graphene composite material.
[0047] The prepared β-FeOOH nanorod-loaded graphene composite material is used to catalyze the degradation of dye pollutants:
[0048] Add 5 mL of 30 wt% H into 100 mL of 200 mg / L dye wastewater. 2 O 2Water and 0.25g of the above-mentioned β-FeOOH nanorod-loaded graphene composite material were reacted under natural light at room temperature. The mixture was mixed evenly with a magnetic stirrer during the reaction. Samples were taken 12 hours after the start of the reaction, and the upper clear liquid was taken and its absorbance was measured. The degradation rate was calculated based on the change in absorbance before and after the reaction. Finally, the removal rates of 200mg / L methylene blue, methyl orange, and rhodamine B dye wastewater were measured to be 99.3%, 97.2%, and 96.0%, respectively.
[0049] Comparative Example 1
[0050] A method for preparing a β-FeOOH nanorod-loaded graphene composite material comprises the following steps:
[0051] (1) adding graphite powder and potassium permanganate in a mass ratio of 1:1 to a mixed acid prepared by sulfuric acid and phosphoric acid in a volume ratio of 8:1, heating and stirring in a water bath at 50°C for 2 hours, then adding hydrogen peroxide to reduce the excess potassium permanganate, filtering the resulting suspension, washing, drying, and grinding into powder to obtain graphene oxide; adding the graphene oxide to N-methylpyrrolidone, ultrasonically dispersing it, adding a hydrazine hydrate solution of the same mass as the graphene oxide for reduction, stirring and reacting at 90°C for 5 hours, filtering, and washing to obtain graphene;
[0052] (2) adding ferric chloride hexahydrate to deionized water to completely dissolve the solution, adding cetyltrimethylammonium bromide twice the mass of ferric chloride hexahydrate, and then adding concentrated ammonia water to adjust the pH to 2, and after ultrasonic dispersion, heating to 90° C. and keeping the temperature for hydrolysis reaction for 16 hours, centrifugation, and drying to obtain β-FeOOH nanorods;
[0053] (3) Add the above graphene into deionized water and stir and disperse evenly to obtain 0.05 g / mL of phosphated graphene dispersion; then add the above β-FeOOH nanorods into deionized water and stir and disperse evenly to obtain 0.1 g / mL of β-FeOOH nanorod dispersion; add the β-FeOOH nanorod dispersion into the graphene dispersion at a volume ratio of 1:6, ultrasonically disperse evenly, react at 150°C for 10 hours, centrifuge, wash, and dry to obtain the β-FeOOH nanorod-loaded graphene composite material.
[0054] The prepared β-FeOOH nanorod-loaded graphene composite material is used to catalyze the degradation of dye pollutants:
[0055] Add 5 mL of 30 wt% H into 100 mL of 200 mg / L dye wastewater. 2 O 2Water and 0.25g of the above-mentioned β-FeOOH nanorod-loaded graphene composite material were reacted under natural light at room temperature. The reaction was mixed evenly with a magnetic stirrer during the reaction. Samples were taken 12 hours after the start of the reaction, and the upper clear liquid was taken and its absorbance was measured. The degradation rate was calculated based on the change in absorbance before and after the reaction. Finally, the removal rates of 200mg / L methylene blue, methyl orange, and rhodamine B dye wastewater were measured to be 75.8%, 70.7%, and 63.5%, respectively.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a composite material of β-FeOOH nanorods loaded with graphene, characterized in that: The steps include: S1, subjecting the amination-treated graphene to a phosphorylation reaction with phosphorous acid and an organic aldehyde to obtain phosphorylated graphene; S2. Adding β-FeOOH nanorods into the dispersion of phosphated graphene to carry out a self-assembly reaction, thereby obtaining the composite material of β-FeOOH nanorods loaded with graphene.
2. The method for preparing the composite material of β-FeOOH nanorods loaded with graphene according to claim 1, characterized in that: In step S1, the amination graphene is obtained by bonding graphene oxide with polyamine and then reducing it; Preferably, the polyamine is at least one of ethylenediamine, butanediamine, hexamethylenediamine or diethylenetriamine.
3. The method for preparing the composite material of β-FeOOH nanorods loaded with graphene according to claim 1 or 2, characterized in that: In step S1, the organic aldehyde is at least one of formaldehyde, acetaldehyde, propionaldehyde or butyraldehyde.
4. The method for preparing the composite material of β-FeOOH nanorods loaded with graphene according to any one of claims 1 to 3, characterized in that: In step S1, the mass ratio of the amination graphene to the phosphorous acid and the organic aldehyde is 1:1-5:1-5.
5. The method for preparing the β-FeOOH nanorod-loaded graphene composite material according to any one of claims 1 to 4, characterized in that: In step S2, the β-FeOOH nanorods are obtained by adding soluble iron salts into water for hydrolysis reaction; Preferably, the hydrolysis reaction further comprises adding a surfactant, and the surfactant is preferably hexadecyltrimethylammonium bromide.
6. The method for preparing the composite material of β-FeOOH nanorods loaded with graphene according to any one of claims 1 to 5, characterized in that: In step S2, the mass ratio of the β-FeOOH nanorods to the phosphated graphene is 1:2-5.
7. The method for preparing the composite material of β-FeOOH nanorods loaded with graphene according to any one of claims 1 to 6, characterized in that: In step S2, the temperature of the self-assembly reaction is 130-160° C. and the time is 6-12 hours.
8. A β-FeOOH nanorod-loaded graphene composite material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the β-FeOOH nanorod-loaded graphene composite material according to claim 8 in catalytic degradation of dye pollutants.